Wykrzykniki a emocje - Krzempek, Monika (Stylistyka, 2021)
The aim of the article is to analyse Polish interjections which can express emotions. The study is situated in the central circle of issues that are undertaken to be examined by contemporary linguistics, humanities and science of the mind. They let us realize the existence of some qualities of interjections which have not been analysed with a more penetrating insight or at length so far. The list of the examined lexemes contains 200 items and was made by using Polish dictionary and The National Polish Language Corpus, which is the basis of this analysis. The collected data show that we can express emotions using expressive interjections. The author also made use of lexemes connected with laughing or crying and other forms which are conceptualized in sound or motion domains, as well as impressive interjections. Their meaning can be modified and intensified by prosody and other grammatical processes and is highly dependent on the context.